Neuroenhancement of Love and Marriage: The Chemicals Between Us - Savulescu, J; Sandberg, A (Springer Science + Business Media B.V., 2008)
This paper reviews the evolutionary history and biology of love and marriage. It examines the current and imminent possibilities of biological manipulation of lust, attraction and attachment, so called neuroenhancement of love. We examine the arguments for and against these biological interventions to influence love. We argue that biological interventions offer an important adjunct to psychosocial interventions, especially given the biological limitations inherent in human love.